Supplementation effect of bypass fat on production performance of lactating crossbred cows - SIROHI, SUNIL K; WALLI, T K; MOHANTA, RANJAN K (The Indian Journal of Animal Sciences, 2010)
Lactating crossbred cattle (10) were randomly divided into 2 groups on the basis of milk yield (14–15 kg/day), day of calving ( 50 days) to see the effect of bypass fat supplementation on nutrient utilization and production performance. Cows were fed wheat straw, concentrate mixture and green maize fodder in the control group and additional 300 g bypass fat was given in treatment group. Experimental feeding was continued up to 90 days after 2 weeks of adaptation. The average milk production and fat corrected milk yield per day was significantly higher in treatment group. Milk fat and total solids content were improved significantly in treatment group, whereas milk protein and solids-not-fat remained unaffected in both groups. The digestibility of nutrients except that of ether extract was comparable in both groups. Intake per kg of milk produced was lower in treatment group than the control group. Milk production efficiency was also significantly higher (30.22%) in bypass fat supplemented in comparison to the control group (27.03%). It was concluded that bypass fat supplementation @300 g/d/animal in medium producing crossbred cows significantly increased the milk production and fat corrected milk yield up to 15.61 and 24.01%, respectively, over the control group.